Facilitators and Barriers to Social Participation of Community-dwelling Older Adults in Iran: A Qualitative Study - Amene Setareh Forouzan; Kian Norouzi Tabrizi; Raziyeh Amini; Farahnaz Mohammadi Shahboulaghi (University of Social Welfare & Rehabilitation Sciences, 2021)
Objectives: Social participation in older adults is one of the key pillars of active aging. Social participation is influenced by multiple underlying factors. The present study aims to explore the facilitators and barriers to social participation in community-dwelling older adults in Iran. Methods & Materials: This is a qualitative study using the grounded theory approach. The study population consisted of community-dwelling older adults. Fifteen samples were selected using a purposive sampling method. Data were collected through in-depth semi-structured interviews. Information were collected until data saturation. Each interview lasted for 45-60 minutes. Analysis was done using the method of Corbin and Strauss (2015). Results: Three main categories and 11 sub-categories were found based on data analysis which were: Participatory elderly (with 5 sub-categories), participatory family (with 2 sub-categories), and community capacity for social participation (with 4 sub-categories). Conclusion: Facilitating social participation of community-dwelling older adults in Iran is associated by individual, family and community. Proper planning should be done in these areas. Providing facilitators for the development of social participation in the elderly can facilitate movement towards active aging.